Analisis Penerapan Akuntansi Pertanggungjawaban Pusat Laba Guna Menilai Kinerja Keuangan Pada KUD Tani Wilis Sendang - Annisatul Asna; Khasanah Sahara; Dewi Wungkus Antasari (Jurnal Kendali Akuntansi, 2023)
The application of responsibility accounting has a very important role, with the aim of evaluating work results and generating feedback so that future cooperative operations can be better. Accountability accounting can help assess financial performance so that the proper use and use of financial resources can be identified. With performance appraisal it can be known the condition of the cooperative in evaluating the results of activities so that it can be used to measure success in KUD Tani Wilis. This study aims to determine the application of profit center responsibility accounting in assessing financial performance. In this study the data used are primary data in the form of an overview, vision and mission, as well as cooperative organizational structure, and secondary data in the form of profit center accountability reports. Sources of data collection in the form of interviews and documentation with quantitative descriptive analysis techniques. The results of this study indicate that the application of responsibility accounting in KUD Tani Wilis is inadequate because it is not fully in accordance with the requirements of responsibility accounting. The results of financial performance in terms of profit center based on the analysis of Gross Profit Margin, Operating Profit Margin, and Net Profit Margin show unfavorable financial performance results. Cooperatives need to implement responsibility accounting in accordance with responsibility accounting requirements by separating controllable and uncontrollable costs, as well as providing account codes for these accounts in the accountability report so that it makes it easier for cooperative managers to control costs and see who is responsible if irregularities occur. Cooperatives must also pay more attention to the increase in cost of goods sold, and minimize production costs and operational costs as well as optimize sales/revenues and evaluate business costs or operational costs, so as to increase profits. By evaluating business costs or operational costs carried out by cooperatives in an effort to increase efficiency where economic resources can be used effectively so that costs are not wasted so that the profits obtained are more optimal and can improve the financial performance of cooperatives.